Development of Axle Load Spectra for Integration in Traffic Characteriaztion for Nigerian Empirical Mechanistic Pavement Analysis and Design Systems - Awosanya, D. O.; Murana, A. A.; Olowosulu, A. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
Design traffic is employed in this research to estimate the expected load repetitions for a given axle load spectrum during the pavement life. In changing traffic characterization in mechanistic-empirical (M-E) design procedure, the process does away with the equivalent single axle load (ESAL) concept and traffic analysis implementation was done by directly using axle load. Comparison of predicted Number of Axle load range repetitions determined by equivalent axle load factor (EALF) and general axle load equivalency factors (GAF), is the main objective. In this study, axle load spectrum by Weigh-In-Motion (WIM) data and parametric standard axle loads which cause equal damage were collected and utilized. Determination of the axle load distribution factor (ALDF) from the WIM data. It is a critical input in the method based on different axle load groups for the estimation of the predicted number of axle load repetitions during the pavement design period. The results that the marked difference on the estimated predicted axle load predictions with the determination of EALF and GAF 63.95% of GAF value for SAST. Similarly, 10.14% for SADT; 30.24% for TADT and 21.43% for TRDT. This indicates the inherited error in the empiricism content in the empirical approach of handling traffic, for the determination of EALF. The estimated traffic prediction value increases as the captured axle load magnitude increased, as a resultant of the type of commodities and goods carried on the roadway pavement.